Melanoma cells resistant towards MAPK inhibitors exhibit reduced TAp73 expression mediating enhanced sensitivity to platinum-based drugs - Makino, Elena (Cell Death Dis, 2018)
The efficacy of targeted MAPK signalling pathway inhibitors (MAPKi) in metastatic melanoma therapy is limited by the development of resistance mechanisms that results in disease relapse. This situation still requires treatment alternatives for melanoma patients with acquired resistance to targeted therapy. We found that melanoma cells, which developed resistance towards MAPKi show an enhanced susceptibility to platinum-based drugs, such as cisplatin and carboplatin. We found that this enhanced susceptibility inversely correlates with the expression level of the p53 family member TAp73. We show that the lower expression of the TAp73 isoform in MAPKi-resistant melanoma cells enhances accumulation of DNA double-strand breaks upon cisplatin and carboplatin treatment by reducing the efficiency of nucleotide excision repair. These data suggest that a subgroup of melanoma patients with acquired resistance to MAPKi treatment and low TAp73 expression can benefit from chemotherapy with platinum-based drugs as a second-line therapy.